Patterns of tasks, patterns of talk: L2 literacy building in university Spanish classes. Issue 2 (4th May 2017) - Gleason, Jesse; Slater, Tammy
ABSTRACT: Second language (L2) classroom research has sought to shed light on the processes and practices that develop L2 learners' abilities [Nunan, D. 2004. Task-based language teaching . London: Continuum; Verplaetse, L. 2014. Using big questions to apprentice students into language-rich classroom practices. TESOL Quarterly, 179, 632–641; Zeungler, J., & Mori, J. 2002. Microanalyses of classroom discourse: A critical consideration of method. Applied Linguistics, 23 (3), 283–288]. Honing in on the micro-level of classroom tasks and even further into the language of the tasks can help to reveal the patterns in teacher- and student-talk that help scaffold students' academic literacy. Literacy, from a systemic functional view of language learning, entails having the tools to function in the social contexts that are valued in students' lives. This study illustrates how grounded ethnography was used in conjunction with functional discourse analysis to illuminate bi-literacy development in two third-year university Spanish writing classes. Findings uncovered unique patterns of tasks and oral interactions that helped build students' academic bi-literacy. While grammar tasks helped build students' knowledge of wording–meaning relationships, culture and writing tasks supported their evolving understanding of how language construes content. This study puts forth a systemic functional curricular model for literacy-based tasks that aims to bridge the previously observed language-content gap.